Desenvolvimento de antenas de microfita miniaturizadas com polarização circular para sistemas de comunicações sem fio - Santos, Heric Weverton dos (2016)
Recently, the growing demand for new technologies in telecommunications has generated much attention from the scientific community. The development of RF systems, the phenomenon of convergence services in a single device and the expansion of wireless communications networks have required the development of new antennas, with low cost, small size and increasingly specific properties. In this context, planar microstrip antennas have been widely used by the industry. In certain mobile communication systems such as radar, satellite, and Global Positioning System (GPS), the use of circularly polarized antennas has gained great emphasis, since, due to their electromagnetic characteristics, the circular polarization enables good performance even in environments subject to severe weather conditions and has small dependence on the misalignment of the transmitting and receiving antennas. This dissertation proposal is based on the analysis and development of single feed miniaturized circularly polarized microstrip antennas. Different techniques are investigated to provide microstrip antennas circular polarization and size miniaturization. In addition, based on theoretical and parametric analyses, new antennas configurations are proposed for applications in wireless communication systems. Several prototypes are built and measured for validation purpose. A good agreement is observed between simulation and measurements results.